Popularizing anise as a future crop - Diwakar, Y; Solanki, R K; Singh, Balraj; Sharma, Y K (Indian Horticulture, 2019)
Anise (Pimpinella anisum) is an annual herbaceous seed spice crop. Native to Mediterranean region, it is cultivated in Turkey, China, Vietnam, Egypt, Spain, Russia, Italy, Greece, Northern Africa, Argentina, Malta, Romania and Syria. Its seeds being economically important are highly valued for chemically composed essential oil content of 1.5-3.5% apart from subsidiary oil yield. Though essential oil is composed of array of pharmaceutically and cosmetically valued chemical constituents, anethole is a major important active ingredient constituting 80-90% of the total essential oil apart from other isomeric constituents like methyl chavicol, anisaldehyde and para-methophenylacentone. Anise seed essential oil being one of the potential sources of natural anethole, other than star anise oil and fennel seed oil, is gaining huge export demand in recent years with advancements in anethole involving pharmaceutical, cosmetic, perfumery and food preparations. The global output of anise essential oil is over 2,500 tonnes (2007) of which, 2,200 tonnes is from China while 300 tonnes is from Vietnam, 12% of the global output of the world.